Family physicians and the mental health system. Report from the Mental Health Supplement to the Ontario Health Survey. - Lesage, A. D. (College of Family Physicians of Canada, 1997)
OBJECTIVE: To determine family physicians' role in the mental health care system. DESIGN: The Mental Health Supplement to the Ontario Health Survey is an epidemiologic, retrospective, home-interview survey. Results reported here are based on responses of a weighted sample of patients aged 15 to 64. SETTING: Ontario, 1990 to 1991. PARTICIPANTS: Random sample of 9953 household residents. MAIN OUTCOME MEASURES: Standardized assessment of mental disorders, associated risk factors and disability, and patterns of use of mental health services. RESULTS: More people seek mental health services from their family physicians (FPs) than from psychiatrists, social workers, or psychologists. Among patients who consulted for mental health purposes, more than 35.4% saw FPs only, 24.7% saw FPs and other mental health care providers (psychiatrists, psychologists, social workers, others), and 40% saw other mental health care providers only. There were few sociodemographic, diagnostic, or clinical severity differences between the FP-only group and the other two groups. Some evidence suggested FPs saw more recent onset cases, but they were also involved in joint care for more complex or disabled cases. More than 57% of those seeing FPs received medication; 43% received other forms of care. Those seeing FPs only made four visits per year; those who consulted other mental health professionals made 14 to 20. CONCLUSIONS: Our study confirms FPs' important role in the current mental health care system.